The Ben Jonson encyclopedia - Brock, D. Heyward (Dewey Heyward), 1941-; Palacas, Maria, 1966- (Rowman and Littlefield, 2016)
"Friend and rival of Shakespeare, Ben Jonson was one of the most learned and interesting men of his age. Throughout his fascinating life, he served not only as a bricklayer but also a soldier, an adventurer, an actor, a poet, and a playwright. The breadth of his experiences, acquaintances, friends, and enemies was legendary, and his literary canon is equally as diverse. The Ben Jonson Encyclopedia covers in detail the works, life, and times of this seminal figure of the English Renaissance. The cross-referenced entries include summaries of all Jonson's plays, masques, and entertainments, as well as sketches of Jonson's friends, enemies, patrons, disciples, actors, and fellow writers. In addition, the book identifies historical figures, mythological characters, and classical authors, as well as Jonson's contemporaries and London place names mentioned in the works. Individuals who danced or participated in the masques and entertainments or tournaments for which Jonson wrote speeches are noted, as are the main actors known to have acted in the plays. All major scholars--from Jonson's own day until the twenty-first century--who have commented on Jonson or his works are also included. An extensive bibliography completes this invaluable scholarly reference tool. Because of Jonson's centrality to--and influence in and beyond--his age, this encyclopedia provides a dynamic, unparalleled vision of the English Renaissance literary scene. Capturing the depth and breadth of Jonson's understanding of early Modern England, The Ben Jonson Encyclopedia will be especially useful for students, librarians, and academics interested in the literary and cultural scene from 1500 to 1650"--Publisher description